Morbidity and Mortality of Low Birth Weight Baby - Bari, MI; Ullah, MA; Khatun, M (TAJ: Journal of Teachers Association, 2009)
This was a prospective study conducted in a cohort of live normal full term singleton newborns delivered in Rajshahi Medical College Hospital with the objective to explore their early neonatal health as well as the role of low birth weight on it. A total 770 live normal newborns were Included in this study. For data collection APGAR Score Estimating Checklist and one protested structured questionnaire were used. Simple descriptive as well as analytical techniques including Chi-square t test were done. The results of this study suggested that low weight (LBW) babies were more prone to develop early neonatal morbidity and mortality than normal birth weight (NBW) babies. LBW infants needed more resuscitation and responded less to resuscitative effort than the infants of NBW. Birth asphyxia was the commonest cause of early neonatal morbidity and mortality. doi: 10.3329/taj.v21i1.3216 TAJ 2008; 21(1): 35-39